“Muerte materna: causas directas e indirectas en el hospital apoyo Iquitos 1988 – 1998” - Vásquez Alva, Wilder (1999)
The objective of this work was detenninar the direct and indirect causes of maternal death in the Hospital support! quitos Cesar Garayar Garcia, during the period of 1988-1990, for this purpose was Wl study of cases and controls with retrospective data collection. Our population and nruestra of study was confonnado by 65 deaths maternal ocWTidos within the period of study, our results confinnan that the rate of mortality maternal is of 23.l by 10, 000n.v. and the tired direct and indirect were:. . DIRECT: Hemorrhage Shock hypovolemic Eclampsia puerperal Sepsis syndrome Help HINTS: disorders cardio vascular Malaria Falciparwn cirrhosis hope that this paper serves as the basis for further studies related to the issue.